Representasi Feminisme dalam Video “So Win”: Sebuah Analisis Wacana Multimodal - Nabilla Kusuma Vardhani; Puteri Felisha Shahnaz (DBSMB, Vocational College of Universitas Gadjah Mada, 2026)
Feminism is one of the oldest social movements that has entered its fourth wave. This wave is closely related to the use of digital media and technology, where feminist issues are disseminated massively through various platforms, such as songs, posters, videos, and so on. One campaign video that voices feminism is